OVERVIEW OF VACCINE-PREVENTABLE DISEASES SURVEILLANCE AND COMPLETE BASIC IMMUNIZATION COVERAGE AT CAMELIA POSYANDU - Wahyuni, Maria Magdalena Dwi; Landi, Soleman; Litelnoni, Aletha Anasthasya; Naisais, Marsela Candra; Tasoin, Asiana Agalta; Yusuf, Dea Benita; Meilyani, Rany (JURNAL WIDYA MEDIKA, 2026)
Vaccine-preventable diseases (VPDs) remain a global health challenge. In Indonesia, immunization coverage has not yet reached the national target, particularly in East Nusa Tenggara Province, which recorded only 79.04% coverage in 2024. This study aimed to describe VPD surveillance and immunization coverage at the Camelia Integrated Health Service Post, involving 30 toddlers, through examination of health cards and interviews. The study used a qualitative approach with a retrospective descriptive analytical design. Surveillance was conducted through five stages: data collection, monthly data processing, analysis, ACER reporting, and follow-up in the form of catch-up immunization. The results showed that 33.3% of children were fully immunized on time, 30% experienced delayed immunization, and 36.7% had incomplete immunization status. DPT-HB-Hib (32.8%) and oral polio vaccine (23%) were the most frequently delayed vaccines due to parents’ lack of knowledge, concerns about side effects, child illness, busy schedules, limited access to services, and insufficient family support. The study concluded that although immunization coverage was not yet optimal, the implementation of VPD surveillance and a consistent catch-up immunization program effectively prevented VPD cases in the Camelia Posyandu area. Recommendations include strengthening digital recording systems, continuing health education, implementing digital reminder systems, optimizing home visits, and conducting periodic evaluations.